2020
DOI: 10.1161/circulationaha.119.043971
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sapien 3 Balloon-Expandable Versus Evolut R Self-Expandable Transcatheter Aortic Valve Implantation in Patients With Aortic Stenosis

Abstract: Background: Two competing transcatheter aortic valve replacement (TAVR) technologies are currently available. Head-to-head comparisons of the relative performances of these 2 devices have been published. However, long-term clinical outcome evaluation remains limited by the number of patients analyzed, in particular, for recent-generation devices. Methods: Based on the French administrative hospital-discharge database, the study collected information for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 31 publications
6
74
2
Order By: Relevance
“…Rates of new PPI across propensity-matched studies were slightly higher when using the Evolut R/PRO valve in comparison with the Sapien 3 valve (23.8% Evolut vs. 18.4% Sapien 3). Three out of 5 studies reported significant differences regarding 30-day or post-procedural new PPI, all of them favoring the Sapien 3 valve (15,17,18). Contrarily, the only randomized trial (19) did not find any differences in PPI rates between the two valves (22.9% Evolut R vs. 19% Sapien 3, P=0.34) ( Figure 1).…”
Section: Sapien 3 Vs Evolut R/promentioning
confidence: 96%
“…Rates of new PPI across propensity-matched studies were slightly higher when using the Evolut R/PRO valve in comparison with the Sapien 3 valve (23.8% Evolut vs. 18.4% Sapien 3). Three out of 5 studies reported significant differences regarding 30-day or post-procedural new PPI, all of them favoring the Sapien 3 valve (15,17,18). Contrarily, the only randomized trial (19) did not find any differences in PPI rates between the two valves (22.9% Evolut R vs. 19% Sapien 3, P=0.34) ( Figure 1).…”
Section: Sapien 3 Vs Evolut R/promentioning
confidence: 96%
“…We included 15 studies—3 RCTs (6-8) and 12 PSM studies (9-11, 17-25)—with 37,958 patients (19,053 with BEV and 18,905 with SEV) (Figure 1). The mean age was 82.6 years and 42.4% were male.…”
Section: Resultsmentioning
confidence: 99%
“…Potential publication bias was examined by visual inspection of the asymmetry in funnel plots. Both the studies of Deharo (11) and Van Belle (9) originated from national registries of French; we extracted data before last quarter 2014 in the study of Van Belle to avoid overlap with the study of Deharo. All meta-analyses were conducted with the R statistical programming environment, version 4.0.0 and the Review Manager, version 5.3, and a 2-tailed P value<0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the exact role of electrophysiological studies, patch ECG recorders, and implantable loop recorders in the management of new-onset LBBB or transient high-degree atrioventricular block should be delineated (Take-home Figure). Moreover, some recent studies questioned the class effect of TAVI, suggesting that not all transcatheter heart valve's designs are equal, especially regarding conduction disturbances 13,14 . Collectively, these observational data, along with the meta-analysis by Faroux et al 12 , should ultimately spur adequately-powered randomized comparisons of the commercially-available valves most commonly implanted in routine practice.…”
Section: New-onset Persistent Left Bundle Branch Block [Lbbb] and Permentioning
confidence: 99%